1992
DOI: 10.3109/02841869209083859
|View full text |Cite
|
Sign up to set email alerts
|

Progestins in Breast Cancer Treatment: A Reveiw

Abstract: The two most widely used synthetic progestins in breast cancer treatment, medroxyprogesterone acetate (MPA) and megestrol acetate (MA), are reviewed with regard to pharmacological, endocrinological and clinical aspects. In high oral doses as second- or first-line endocrine therapy in advanced breast cancer, they give a similar response rate as tamoxifen (TAM) and aminoglutethimide (AG). The mechanism of action is probably complex. Considerable changes in serum levels of different hormones are induced by proges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 106 publications
0
15
0
2
Order By: Relevance
“…64,65 Progestins have similar RRs to tamoxifen. 66,67 They represent a useful option in some patients, but are associated with significant weight gain, fluid retention, vaginal bleeding, and risk of thromboembolic events. 65,68 The AIs anastrozole and exemestane were shown to be marginally superior to MA in terms of survival in initial trials, as shown in Table 1.…”
Section: Schiavon and Smithmentioning
confidence: 99%
“…64,65 Progestins have similar RRs to tamoxifen. 66,67 They represent a useful option in some patients, but are associated with significant weight gain, fluid retention, vaginal bleeding, and risk of thromboembolic events. 65,68 The AIs anastrozole and exemestane were shown to be marginally superior to MA in terms of survival in initial trials, as shown in Table 1.…”
Section: Schiavon and Smithmentioning
confidence: 99%
“…Megestrol acetate was about as effective as aminoglethimide for breast cancer treatment [70]. While the mechanism by which megestrol acetate executed its anti-tumour effects are incompletely understood [71], due to suppression of adrenal steroid synthesis treatment with megestrol acetate suppressed plasma estrogen levels to about the same degree as aminoglutethimide [72] This, however, did not induce cross-resistance between megestrol acetate and aromatase inhibitors [71,73].…”
Section: Explanation To Lack Of Cross-resistance Between Steroidal Anmentioning
confidence: 99%
“…Recently, a randomised study revealed treatment with letrozole 2.5 mg daily to be superior to aminoglutethimide 500 mg daily (Gershanovich et al 1998). While the full mechanism of the anti-tumour action of progestins administered in high doses to breast cancer patients is not understood (Lundgren 1992), it is now clear that megestrol acetate 160 mg daily suppresses plasma oestrogen levels by 75-80% in postmenopausal women (Lundgren et al 1996). Recent studies have shown that letrozole given as 2.5 mg daily produces a better response rate compared with megestrol acetate (Dombernowsky et al 1998).…”
Section: The Importance Of Potent Oestrogen Suppressionmentioning
confidence: 99%